Celluloid revolt : German screen cultures and the long 1968 - Gerhardt, Christina; Abel, Marco (Screen cultures : German film and the visual, 2019)
"The epoch-making revolutionary period universally known in Germany as '68 can be argued to have predated that year and to have extended well into the 1970s. It continues to affect German society and culture to this day. Yet while scholars have written extensively about 1968 and the cinema of other countries, relatively little sustained scholarly attention has thus far been paid to 1968 and West German, East German, and Austrian cinemas. Now, five decades later, Celluloid Revolt sets out to redress that situation, generating new insights into what constituted German cinema around 1968 and beyond. Contributors engage a range of cinemas, spanning experimental and avant-garde cinema, installations and exhibits; short films, animated films, and crime films; collectively produced cinemas, feminist films, and Arbeiterfilme (workers' films); as well as their relationship to cinemas of other countries, such as French cinéma vérité and US direct cinema"--